Bounds and Majorization Relations for the Zeros of a Class of Fibonacci-Type Polynomials. (1st February 2016) - Kittaneh, Fuad
ABSTRACT: We apply certain matrix inequalities involving eigenvalues, the numerical radius, and the spectral radius to obtain new bounds and majorization relations for the zeros of a class of Fibonacci-type polynomials. Our results improve upon some earlier bounds for the zeros of these polynomials.